COVID-19 Effect on Accelerating Technology and Innovation in Businesses - Arman, Husam; Al-Fulaij, Shaikha; Al-Qudsi , Sulayman; Alawadhi, Ahmad; Al Ali, Mohammad (Organizations and Markets in Emerging Economies, 2024)
This paper assesses empirically the COVID-19 effect on businesses and the potential dynamic changes regarding post-COVID-19 automation and technology penetration using various logistic regression models. A field survey was used to collect the necessary data for testing various hypotheses. This study demonstrates the severity of the pandemic on businesses and how it has changed their perspectives on technology as a critical aspect of survival and future success. The results showed that capital-intensive firms are more resilient to the crisis. In addition, the firms that were affected severely in terms of employment due to the pandemic believe that technology will significantly impact hiring, investment, and value added. This paper investigates a unique phenomenon represented by COVID-19, its impact on businesses in a resource-rich context and their responsiveness concerning technology deployment and automation.